2000
DOI: 10.1159/000045541
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Mesothelioma and Membranous Nephropathy

Abstract: Underlying malignancy has been thought to be responsible for 5–10% of the cases of membranous nephropathy in adults, with the risk being highest in patients over the age of 60 years. Solid tumors such as carcinomas of lung or colon, are most often involved. It is presumed that tumor antigens are deposited in the glomeruli; this is followed by antibody deposition and complement activation, leading to epithelial cell and basement membrane injury and proteinuria due to the associated increase in glomerular permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…As shown in Figure 4, the antibody titers the antibody titers were examined by the ELISA system against 6 synthesized peptides of Gene-X and THBS-2. As shown in Figure 4, the antibody titers of Gene-X [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and THBS-2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were well correlated with the results by phage plaque assay. Therefore, antibody titers against Gene-X 40-59 and THBS-2 [26][27][28][29][30][31][32][33][34][35]…”
Section: Immunohistochemical Detection Of B Cells In the Tumor Specimmentioning
confidence: 85%
See 3 more Smart Citations
“…As shown in Figure 4, the antibody titers the antibody titers were examined by the ELISA system against 6 synthesized peptides of Gene-X and THBS-2. As shown in Figure 4, the antibody titers of Gene-X [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and THBS-2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were well correlated with the results by phage plaque assay. Therefore, antibody titers against Gene-X 40-59 and THBS-2 [26][27][28][29][30][31][32][33][34][35]…”
Section: Immunohistochemical Detection Of B Cells In the Tumor Specimmentioning
confidence: 85%
“…Moreover, membranous nephropathy had been reported to be associated with MPM. (40,41) The causal relationship between IFT-88 and membranous nephropathy should therefore be elucidated in a further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a review of the English literature identified seven reported cases of malignant mesothelioma associated with nephrotic syndrome (3)(4)(5)(6)(7)(8)(9). Among these seven cases, the primary site of mesothelioma was the pleura in five cases, peritoneum in one case and tunica vaginalis testis in one case.…”
Section: Discussionmentioning
confidence: 99%